Chinese students' group work performance: does team personality composition matter?. Issue 3 (20th March 2019) - Lau, Kwok Hung; Jin, Qian
Abstract : Purpose: The purpose of this paper is to investigate if team personality composition has any effect on group work performance of undergraduate students in China. Design/methodology/approach: Using a questionnaire based on the Big-Five framework to collect data on personality traits, this study investigated whether in the Chinese education setting overall effectiveness of university students working in groups was related to the different personalities of the group members. Students of two undergraduate business programs jointly run by an Australian university and a Chinese university in Shanghai participated in the research. Findings: The findings reveal that aggregated personality traits have no effect on team effectiveness but homogeneity in emotional stability among group members does have a positive impact on group performance. Based on a comprehensive review of studies concerning the Chinese education approach, it is believed that the outcome of this study may reflect to a certain extent the influence of traditional learning method on how university students interact with team members in group work hence affecting group performance. Research limitations/implications: This study has surveyed 166 undergraduate students on their personality traits and performance in group work. A larger sample size can help improve the generalizability of the findings. Practical implications: The findings of this study shed light on how group work can be used more effectively in learning through proper assessment task design and guidance from the facilitator. Social implications: The outcome of this research also provides insight on how group work in higher education can better prepare students for the Chinese workforce. Originality/value: While studies on relationship between personality mix and team effectiveness in business setting are plenty, there is relatively little research on how team personality composition can impact on group performance in education especially in Asian countries. This study is one of the first attempts to supplement the inadequacy in this regard.